Implementing short stories in language teaching and learning (SCIENCE and SOCIETY, 2024)
This article analyzes the learning process which utilizes short stories to improve students’ interaction skills in English. In particular, the features of using the narrative literary genre in improving four skills (listening, reading, speaking, writing) of students were examined.